Educaplay como estrategia didáctica en el proceso de enseñanza-aprendizaje de la asignatura de Ciencias Naturales en los estudiantes de cuarto año de EGB de la Unidad Educativa San Miguel, del cantón San Miguel de Bolívar, provincia Bolívar, durante el año lectivo 2024-2025. - Calero Carrera, José Antonio (2025)
This research analyzes the influence of the Educaplay platform as a didactic strategy in the teaching-learning process of the Natural Sciences subject for fourth-year EGB students at Unidad Educativa San Miguel, located in the San Miguel canton of Bolívar province, during the 2024–2025 academic year. The study arises from the need to recover students' interest and motivation, which have been affected by a mistaken perception of the subject. Despite the teacher's efforts, methodologies focused on memorization and theoretical exposition are still being used. The applied methodology followed a mixed approach. Quantitatively, a survey was conducted with 26 students, and qualitatively, an interview was carried out with the subject teacher. The results confirm that the use of Educaplay, through word searches, crosswords, and interactive games, significantly increases student motivation, improves content comprehension, and promotes more active participation. It is concluded, therefore, that the careful and planned integration of digital resources such as Educaplay can help transform the traditional pedagogical approach into one that is more dynamic, interactive, and meaningful.